Building life cycle assessment research: A review by bibliometric analysis - Geng, Shengnan; Wang, Yuan; Zuo, Jian; Zhou, Zhihua; Du, Huibin; Mao, Guozhu (Renewable & sustainable energy reviews, 2017)
This study aims to examine the literature related to the building life cycle assessment (LCA) that are published from 2000 to 2014 by means of bibliometric methods based on databases of the Science Citation Index and Social Science Citation Index. Of 2025 retrieved publications, 95% were journal articles. The patterns of these articles were investigated such as subject categories, journals, countries, institutions, hot topics and the most highly cited articles. The results showed a rapid growth of building LCA related publications with the USA being the leading country in terms of contributing to the largest number of articles and possessing the greatest influence. Norwegian University Science and Technology is the leading university in terms of building LCA research, which is followed by University of California at Berkeley. All the top 15 institutions possess a favorable cooperative relationship with other institutions. Most journal articles were associated with energy (521 articles), followed by material (388), sustainability (304), carbon (299) and technology with 180. According to the comprehensive analysis of the keywords, it can be concluded that subtopics such as energy, materials, environmental impacts and sustainable development will be prominent directions of future building LCA research, while life cycle costing and life cycle inventory will continue to be the common research methods. These findings help to identify hotspots in the building LCA research. Similarly, this study provides useful inputs for the decision making on the subtopic selection and publication strategy in the building LCA research.